Enhanced solar thermal conversion performance of plasmonic gold dimer nanofluids. (September 2020) - Chen, Zhuo; Chen, Meijie; Yan, Hongjie; Zhou, Ping; Chen, XingYu
Highlights: Coupled effect between rod and sphere can enhance solar absorption ability. An enhancement of solar absorption efficiency of 21.2% can be obtained for dimer. Collector parameters should be designed to balance temperature and efficiency. Abstract: Volumetric solar thermal conversion is an emerging technique for a plethora of applications such as solar thermal power generation, desalination, and solar water splitting. However, achieving broadband solar thermal absorption via dilute nanofluids is still a daunting challenge since the absorption peaks of common metal particles usually locate in the visible part. The coupled effect of different nanoparticles should be enhanced in the broadband spectrum to improve the solar thermal conversion performance. Hence, in this work, enhanced volumetric solar thermal conversion performance is demonstrated over a thin layer of the proposed plasmonic dimer nanofluid, which consists of the rod and sphere in the water. The underlying mechanism is found to be the photonic superposition of local surface plasmon resonance, propagating surface plasmon resonance, and gap resonances at different wavelengths. The solar absorption efficiency of the dimer nanofluid can be improved as high as 21.2% compared with the blended nanofluid at the same number of sphere and rod. The various location of sphere in the dimer system in the synthesis process may lead to the slight red or blue shift, which would result in the more broadband absorption spectrum and further enhance the solar thermal conversions applications. Further the calculation results based on the direct absorption solar collector show both the collector efficiency and temperature increase of the dimer nanofluid are greater than that of the blended nanofluid. This work provides a dimer candidate to enhance volumetric solar absorption performance for efficient solar thermal conversion applications.